THE USE OF SHORT ANIMATION MOVIES AS A LEARNING MEDIA TO IMPROVE STUDENTS' VOCABULARY ACQUISITION - Liya, Ade; Lekatompessy, Jeny; Patty, Jusak (Pattimura Excellence Journal of Language and Culture, 2024)
This study aimed to finding out know how short animation movies improve students' vocabulary acquisition and students' perceptions of the used short animation movies to improved students' vocabulary acquisition. This study implemented classroom action research (CAR) with 24 students of VIII-B Grade at SMP Negeri 9 Seram Bagian Timur, 2023–2024 academic years. To conduct the data, the researcher conducted Test, Observation and Survey. After that, the data were analysed quantitatively and qualitatively. The result showed that in pre-test in cycle I student’s average of test was 30.83 post-test was 62.50 indicating this study did not achieved criteria of success. So, this study was contine to cycle II. The result showed that post-test in cycle II has improved student’s average of test to 86.67 and the students achieved the criteria of success. The success of used short animation movies in improving students' vocabulary has been explained by several factors. First, short animation movies (Kung Fu Panda, Toy Story, and Zootopie) present basic vocabulary in an interesting context, and the storyline was easy for students to understand, making it easier for them to understand and remember the meaning of the vocabulary. Second, structured pre-watching, watching, and post-watching activities helped students prepare, be actively involved, and deepen their understanding of the vocabulary being studied. Apart from that student's results of vocabulary show that nouns have the highest increase with an average score (92) followed by verbs (92) and adjectives (85). Students’ perception of the used short animation movies as a learning media to improve vocabulary acquisition got received a very positive response from the majority of students.